Abnormalities of the blink reflex in Gilles de la Tourette syndrome. - Smith, S J (1989)
The blink reflex and it's recovery cycle were studied in 26 patients with Gilles de la Tourette syndrome and 10 controls. There was a significant increase in the mean duration of the R2 response. The amplitude of the R2 response following paired shocks (mean R2[T]/R2[C]%) was 11%, 40% and 52% of the conditioning stimulus with intervals of 200 ms, 500 ms and 1 second in the patients, compared with 10%, 17% and 32% respectively in the controls. Half the patients, however, had normal recovery cycles and voluntary suppression of tics and blinks reduced the amplitude of R2 in all patients. These results suggest increased excitability of brainstem interneurons in Gilles de la Tourette syndrome.